2004
DOI: 10.1177/0010880404265351
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Skills, and Abilities for Lodging Management

Abstract: This study examines the effect of the following knowledge, skills, and abilities (KSAs) on managers’ lodging success: human resources management, marketing, financial management, and information technology. The investigation determined that knowledge perceived as important for management success differs from actual KSAs that distinguish senior-level executives from their subordinate middle-level counter-parts. The findings revealed that managers placed highest importance on and were most skilled in human resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 9 publications
3
73
0
7
Order By: Relevance
“…Intrinsic attributes, personal character, strategic positioning, lucky breaks, professional certification and college and graduate degrees will be perceived as important for management success by lodging professionals and rated higher than other prior identified KSA requisites (human resources and financial management, marketing, and information technology) reported in the Kay and Moncarz (2004) study.…”
Section: Current Study and Research Hypothesesmentioning
confidence: 68%
See 2 more Smart Citations
“…Intrinsic attributes, personal character, strategic positioning, lucky breaks, professional certification and college and graduate degrees will be perceived as important for management success by lodging professionals and rated higher than other prior identified KSA requisites (human resources and financial management, marketing, and information technology) reported in the Kay and Moncarz (2004) study.…”
Section: Current Study and Research Hypothesesmentioning
confidence: 68%
“…Competencies in such areas as financial management are emerging as newly identified requisites for management success (Woods et al, 1998;Chung, 2000;Kay and Moncarz, 2004). For example, a recent study by Kay and Moncarz (2004) examining lodging management knowledge, skills and abilities (KSAs) found that financial management is a significant indicator of management the relationships among departments and assessing employee concerns and the organization's climate. In another article by Cornell (2000) on managers' job-related competencies, it was found that professional appearance and poise, and face-to-face communications were rated higher by GMs than by subordinate managers (Kay and Russette, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations with a focus on small businesses are increasing, and they establish the importance of knowledge for entrepreneurship and innovation (Zeng, Xie & Tam, 2010;Gast, Werner, & Kraus, 2017). Selfefficacy, knowledge, skills and abilities affect the workload, the interest and level of difficulty of the targets that are established for performance; they also influence persistence (Kay & Moncarz, 2004). Studies have identified two important characteristics that are positively related to influencing one's starting one's own business and to the business performance, which are self-confidence in one's knowledge and skills and relationships with other people who will transmit knowledge (knowledge-based resources) (De Clercq & Arenius, 2006;Wiklund & Shepherd, 2003;Lee, Lee & Pennings, 2001;Arenius & Minniti, 2005;Autio & Wennberg, 2010).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…For example, technical competencies like using MS Office Software, sales skills, using front desk equipment/software, IT skills and the competency of financial planning/budgeting skills both technical and administrative corresponded to the some competencies which Kay and Morkarz (2004) appointed in their study to some degree. A closer study in form by Millar, Mao and Moreo (2008) were bringing the same issue to the fore.…”
Section: Having It Skills Technicalmentioning
confidence: 99%